2009
DOI: 10.1074/jbc.m808261200
|View full text |Cite
|
Sign up to set email alerts
|

Three Promoters Regulate Tissue- and Cell Type-specific Expression of Murine Interleukin-1 Receptor Type I

Abstract: The type 1 interleukin-1 receptor (IL-1R1) mediates diverse functions of interleukin-1 (IL-1) in the nervous, immune, and neuroendocrine systems. It has been suggested previously that the versatile functions of IL-1 may in part be conferred by the multiple promoters of IL-1R1 that have been identified for the human IL-1R1 gene. Promoters for murine IL-1R1 (mIL-1R1) gene have not been studied in detail. We performed 5-rapid amplification of cDNA ends to determine the transcription start sites (TSS) in mIL-1R1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…They are represented in green, purple, blue, and red in Table 1 Three of the clusters (TSS1, TSS2, and TSS3) are in agreement with our previous study (14), although >30 additional bases of the 5′ UTR regions in two of the three clusters were uncovered by the current method. Importantly, a unique fourth TSS cluster was identified.…”
Section: Resultssupporting
confidence: 75%
“…They are represented in green, purple, blue, and red in Table 1 Three of the clusters (TSS1, TSS2, and TSS3) are in agreement with our previous study (14), although >30 additional bases of the 5′ UTR regions in two of the three clusters were uncovered by the current method. Importantly, a unique fourth TSS cluster was identified.…”
Section: Resultssupporting
confidence: 75%
“…Inspection of the core promoter sequences showed no TATA box consensus sequence in any of the hIL-1R1 promoters. This is consistent with previous reports that IL-1R1 uses TATA-less promoters 15,16. Other studies have demonstrated that TATA-less promoters often start transcription from several TSSs downstream of the promoter 18.…”
Section: Discussionsupporting
confidence: 93%
“…We showed in a recent study, that three different promoters control murine IL-1R1 (mIL-1R1) expression in a tissue- and cell type-specific manner, 15 suggesting that the regulation of IL-1R1 by multiple promoters is an important mechanism for controlling the diverse functions of IL-1R1. Screening transcription start sites of mIL-1R1 from a large panel of different tissue samples was necessary for the discovery of these mIL-1R1 promoters because some promoters are not active in all tissues.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we thoroughly investigated the existence of multiple IL-1R1 promoters. Using the sensitive CapFishing method in combination with nested PCR, we ultimately found 4 murine and 7 human IL-1R1 promoters (Chen et al, 2009; Li et al., 2010). In neurons, IL-1R1 in the mouse is driven by two different promoters that are not active in the non-neuronal cell types.…”
Section: The Diverse Sources Targets and Contrasting Functions Of Imentioning
confidence: 99%
“…It is likely that the neurophysiological functions of IL-1 are mediated by neuronal specific IL-1 receptors and their non-inflammatory signaling pathways. Furthermore, in vitro promoter–reporter analysis shows different IL-1R1 promoters are differentially regulated by glucocorticoids, suggesting responsiveness to IL-1 could be differentially regulated in different cell types by modulating hormones (Chen et al, 2009). The distinct cell type specific actions of IL-1 on various CNS cells can also be demonstrated in cultured CNS cell lines (An et al, 2011).…”
Section: The Diverse Sources Targets and Contrasting Functions Of Imentioning
confidence: 99%